Portfólio Tecnológico: apresentação dos Serviços de Tecnologia e Inovação (STI) do SENAI/MA. - ARAÚJO, Diego Reis (2024)
The day-to-day lives of companies over the years have been impacted by changes in market behavior, resulting from each historical milestone: industrial revolution, New York stock market crash, Second World War, globalization and the Coronavirus pandemic. These facts implied the need for changes in organizations' strategies and operations. Going through this scenario, the National Industrial Learning Service of the State of Maranhão (SENAI/MA), in addition to offering learning courses, which places it as one of the main national institutions in the subject, began in 2010 to work with consultancies through the Technology and Innovation Service (STI), operating throughout the State of Maranhão with personalized services according to the expertise of its consultants. However, despite annual growth, the STI sector realizes that the absence of a digital product weakens it market-wise and institutionally. With this in mind, the present work aims to develop a Technological Portfolio for external visibility of Consultancies in the Technology and Innovation Services Sector (STI), of the National Industrial Learning Service (SENAI). This work also seeks to answer the following research problem: What initiative can SENAI/MA take to achieve gains in the digital market, create alternatives for prospecting and structure Consulting solutions for the Technology and Innovation Services Sector (STI)? In the methodology, the following steps were carried out: process mapping and stakeholder awareness, bibliographical research, prototype creation and discussion with the STI sector Coordination (COTEI), construction of Figma, presentation meetings and discussion of improvements and application of a questionnaire validation with stakeholders. As a result, the Technological Portfolio was built, which received approval from stakeholders and was recognized as a vector for potentializing access to new markets and generating new business, as well as a means for standardizing and structuring the STI sector.